Public Infrastructure Procurement Practice and Challenges in the Bamenda Municipality, North West Region Cameroon - Ngong, Hycinth Ndze; Fombe, Lawrence F.; Achankeng, Eric; Fombe, Georgewill M. (Advances in Social Sciences Research Journal, 2021)
Public infrastructures play a significant role in poverty reduction, human development and spatial interaction of the population. The practices of stakeholders in the procurement system in Bamenda are a controversy in the contemporary socio-political discourse. Through these practices, public infrastructures are provided to and for the population. This paper seeks to uncover the myriad of challenges involved in the procurement practices in Bamenda. The study made use of both qualitative and quantitative data, obtained using secondary and primary sources from documentary exploration and extensive field work. Secondary sources included books, annual reports and archives of Divisional and Regional Delegations, Inspectorates of Education, Regional Institute of Statistics and Public Contracts Regulatory Agency, North West amongst others. Primary data was obtained over three months of extensive field investigations through questionnaires interviews and focus group discussions. A GPS was utilized to obtain geographic coordinates of publicly procured infrastructures, particularly health, educational and road infrastructures. Results reveal that there is complexity in the way procurement is undertaken for socio-economic benefits to the population. Procurement principles are ineffectively applied, leading to inefficient execution of contracts. Late payment of contract funds amongst others is a cause of inefficient execution and lateness in the delivery of procurement output in the domains of health, roads and educational infrastructures. The study recommends project owners to release contract funds earlier than usual and contractors who enhance poor execution of projects and uncivil road users who facilitate road degradation or cause damages to projects be severely sanctioned. The Law No. 73/7 of 7 December 1973 on the preferential claim of the treasury to safeguard public funds by Municipal and Regional Councils should be effectively implemented.